PENGARUH SUBTITUSI BAHAN ANORGANIK PLASTIK TERHADAP KUAT TEKAN BETON NORMAL - Azwanda Azwanda; Samsunan Samsunan; Helba Destha Rangga (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
The waste of used plastic bottles is the material that is widely found in the environment as waste of drinking water. The existence of this material used as a substitute for sand into a concrete mixture. The plastic bottle is further processed in certain way that it becomes fiber. The purpose of this research is to know the influence of the use of plastic material as a substitute of sand to the compressive strength of concrete. The benefits of this research can reduce the environmental impact on plastic bottles used as concrete mixtures. The research was conducted by laboratory experimental method to get the data followed by analysis to obtain the result of compressive strength. The aggregate used is crushed stone with a maximum aggregate diameter of 25 mm. The planned concrete quality of K-250 with Water Cement Ratio (FAS) is 0.60. The specimens used were cylinders with diameter 15 cm, H = 30 cm with total 24 pieces. This research was conducted to describe the development of compressive strength on concrete by using substitution (replacement) some sand with inorganic materials as much as 0.5%, 1%, 1.5%. As comparison made of normal specimens 0% (without plastic substitution). The compressive strength test was performed at 7 days and 28 days. The largest average compressive strength at the age of 7 days is on the use of 0% that is 15.396 MPa. Furthermore, for the age of 28 days has the largest average compressive strength of 20.592 MPa at a percentage of 0%. There was a decrease of concrete compressive strength with substitution testing of plastic materials of 0.5%, 1%, and 1.5% respectively. From the test results, the more percentage of substitution of plastic material added in the concrete mixture, the compressive strength decreased. Keywords : Anorganic, Compressive Strength, Normal Concrete